Russia between East and West - Lukin Alexander (Međunarodni Problemi, 2003)
The East and West have been symbols in Russian culture for centuries and have served as reference points for Russians in their search of cultural and geopolitical identity. They continue this role in contemporary Russia. Should Russia be part of the East or West? Russian politicians, scholars, writers and thinkers have been this question for several hundred years. While no agreement has yet been reached the discussion, far from purely academic, has had practical political consequences. The political position and practical policy agenda of a contemporary Russian politician or any other member of the educated elite still depends largely on where he or she places Russia on the East-West axis of the geopolitical compass and where he or she wants to see the needle point in the future.